ИССЛЕДОВАНИЕ ВЫСОКОЧУВСТВИТЕЛЬНОГО ФОТОПРИЕМНОГО УСТРОЙСТВА НА ОСНОВЕ ЛАВИННОГО ФОТОДИОДА ДЛЯ ОПТОЭЛЕКТРОННЫХ ИЗМЕРИТЕЛЬНЫХ СИСТЕМ - Брагинец, И.А.; Кононенко, А.Г.; Масюренко, Ю.А. (Інститут електродинаміки НАН України, Київ, 2016)
The authors have considered requirements to photo receiving devices (PhRD) of optical systems on the laser rangefinder basis for measurement of the linear displacements of the diffuse reflecting objects. They investigated the scheme of PhRD on the avalanche photo diode basis and carried out light and energetic calculation. They determined of a signal to noise relation at the exit of PhRD by analytical and the experimental way and also estimated potential measurement accuracy of the linear displacements. Application of the received results will give the chance to increase accuracy of non-contact measurement of movements and vibrations of the diffuse reflecting objects at small basic distances. References 8, tables 2, figures 4.